Mitigating Trade-Related CO2 Emissions: The Role of Renewable Energy, Environmental Technologies, and Policy Stringency in BRICS Countries: A PMG-ARDL Analysis - Hamrouni, Daghbagi (International Journal of Energy Economics and Policy, 2025)
Trade plays a pivotal role in the economic growth and development of BRICS countries, yet it also significantly contributes to CO2 emissions and environmental degradation. This study aims to investigate the effectiveness of renewable energy, environmentally-related technologies, and environmental policy stringency in mitigating the detrimental effects of trade on CO2 emissions within the BRICS countries from 2000 to 2020. Utilizing panel data and the PMG-ARDL approach, we examine the long-term and short-term impacts of industrial value-added, trade, population, renewable energy, non-renewable energy, environmental-related technology, policy stringency, and geopolitical risk on CO2 emissions. Our findings reveal that, in the long term, industrial growth, population growth, trade, and non-renewable energy consumption exert a significant and positive influence on CO2 emissions. Conversely, renewable energy, environment-related technologies, and geopolitical risk play a significant and negative impact on emissions. Crucially, our results highlight that renewable energy and environment-related technologies effectively mitigate the adverse effects of trade on pollution. In contrast, the interaction between trade and environmental policy stringency exhibits no statistically significant impact. These findings show the critical role of renewable energy and environment-related technologies in fostering sustainable development and mitigating the environmental repercussions of trade within the BRICS context, providing valuable insights for policymakers in these economies.